Technical Proficiency Analysis in Table Tennis: A Comparative Study Between Advanced and Intermediate Players - Benny Aprial; Denny Setyawan; George Danut Mocanu; Candra Brema Tarigan; Ghulam Mustafa; John Michael D. Aquino; Bilal Azmi Sarıtaş (INSPIREE: Indonesian Sport Innovation Review, 2025)
The  purpose  of  the study. This study presents a comprehensive examination of technical proficiencies in table tennis, comparing advanced and intermediate players to identify key differentiating factors in performance. Materials and methods. The research involved 40 participants (20 advanced players with 5+ years of competitive experience and 20 intermediate players with 2-4 years of experience) aged 18-25 years. Over a three-month period, participants underwent systematic evaluation of their technical skills, including basic stroke accuracy, biomechanical efficiency, and tactical adaptability. This empirical investigation was undertaken at seven Table Tennis clubs located within the confines of Medan city, Indonesia. Results. Results revealed significant differences between skill levels in most measured parameters: advanced players demonstrated superior forehand drive accuracy (85.3% vs 67.1%, p<0.001), backhand drive accuracy (82.7% vs 63.4%, p<0.001), and rally consistency (28.4 vs 15.6 hits, p<0.001). Biomechanical analysis showed advanced players maintained more optimal arm angles (110.5° vs 95.8°) and faster bat swing speeds (17.8 m/s vs 12.4 m/s). Additionally, advanced players exhibited better tactical adaptation, with more service variations (6.8 vs 4.2 types) and faster reaction times (245ms vs 312ms). Conclusions. The findings highlight that the progression from intermediate to advanced level requires improvements across multiple domains, including technical consistency, biomechanical efficiency, and tactical adaptability. This research provides valuable insights for developing targeted training programs and understanding the multifaceted nature of expertise in table tennis.